Flexible and Transferable Silver Nanowire Liquid Crystal Polymer Film Obtained via Photo‐Alignment Programming (Advanced Optical Materials 16/2022). Issue 16 (18th August 2022) - Sang, Jingxin; Zhang, Juan; Feng, Hange; Sun, Jiatong; Shang, Jianhua; Zhang, Yihong; Zhao, Shuguang; Neyts, Kristiaan; Chigrinov, Vladimir
Abstract : A non‐contact photo‐alignment technology was proposed to align silver nanowires (AgNWs) in a liquid crystal polymer (LCP) film with high order parameter. They are controlled to have planar alignment and twisted nematic structures in micro‐multi‐domains. The aligned AgNWs can be used to improve the mechanical properties of LCP films. The AgNW/LCP film can be programmed by micro‐multi‐domain photo‐alignment for use in flexible and wearable devices. For further details see article number 2200950 by Jiatong Sun and co‐workers.